2010
DOI: 10.4209/aaqr.2009.09.0059
|View full text |Cite
|
Sign up to set email alerts
|

Dry and Wet Deposition of Polychlorinated Dibenzo-p-dioxins and Dibenzofurans on the Drinking Water Treatment Plant

Abstract: This study investigated the concentrations and congener profiles of polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) in intake source water (source water) and tap drinking water (tap water) of drinking water treatment plants (DWTPs). In order to have a better understanding on the influence of atmospheric PCDD/F deposition on drinking water, PCDD/Fs in the ambient air of a DWTP (DWTP-LN) were measured and both dry and wet deposition on the water treatment facilities were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
6
19
0
Order By: Relevance
“…When comparing atmospheric concentrations between the two seasons, the total I-TEQ concentration in fall was higher by a factor of 1.6-1.8 than in spring, probably (Shih et al, 2006;Lin et al, 2010;Huang et al, 2011). OCDD was the most abundant congener found in all atmospheric samples with an average contribution of 21-27% of the total PCDD/F concentration at sites I, A, and R, and for 42% at site B followed by 1,2,3,4,6,7,OCDF,and 1,2,3,4,6,7, Note that the total PCDF concentration was significantly higher than PCDDs except at site B in the fall, probably because of its high proportion of OCDD (42%).…”
Section: Ambient Air Pcdd/f and Pcb Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing atmospheric concentrations between the two seasons, the total I-TEQ concentration in fall was higher by a factor of 1.6-1.8 than in spring, probably (Shih et al, 2006;Lin et al, 2010;Huang et al, 2011). OCDD was the most abundant congener found in all atmospheric samples with an average contribution of 21-27% of the total PCDD/F concentration at sites I, A, and R, and for 42% at site B followed by 1,2,3,4,6,7,OCDF,and 1,2,3,4,6,7, Note that the total PCDF concentration was significantly higher than PCDDs except at site B in the fall, probably because of its high proportion of OCDD (42%).…”
Section: Ambient Air Pcdd/f and Pcb Concentrationsmentioning
confidence: 99%
“…Pankow (1991), Pankow (1994), and Pankow and Bidleman, (1992) have been used to calculate the gas-particle partitioning of SOCs (especially for PAHs). Since PCDD/Fs, PCBs, and PAHs are all SOCs with similar properties, equations which have been successfully used to describe gas-particle partitioning of PCDD/Fs and PCBs by several researchers (Mandalakis et al, 2002;Mandalakis and Stephanou, 2007;Lin et al, 2010;Wang et al, 2010b).…”
Section: Sampling and Analysismentioning
confidence: 99%
“…(1)- (3), based research by Pankow (1991), Pankow (1994), and Pankow and Bidleman, (1992) have been used to calculate the gas-particle partitioning of semivolatile organic compounds (especially for PAHs). Since PCDD/Fs and PAHs are all semivolatile organic compounds, equations which have been successfully used to describe gas-particle partitioning of PCDD/Fs by several researchers (Lohmann and Jones, 1998;Wu et al, 2009;Xu et al, 2009;Lin et al, 2010a;Wang et al, 2010).…”
Section: Gas-particle Partitioningmentioning
confidence: 99%
“…Results indicated that the dry deposition of PCDD/Fs is more important than the wet deposition of PCDD/Fs to the total PCDD/F distribution in the environment. In addition, significant influence of atmospheric deposition of PCDD/Fs on tap drinking water has been addressed (Lin et al, 2010a). Therefore, knowledge of the characteristics of PCDD/Fs deposition is essential for observing subsequent fate of PCDD/Fs in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) generate toxicological effects and associated adverse health implications to organisms (U.S. EPA, 2003;Lin et al, 2010a;Ning and Sioutas, 2010). PCDD/Fs were first found in the fly ash of a municipal solid waste incinerator (MSWI) (Olie et al, 1977).…”
Section: Introductionmentioning
confidence: 99%